Integrating Realistic Mathematics Education with Think Pair Share to Enhance Problem-Solving Ability and Mathematical Beliefs in Integer Learning - Alfisyahrina, Munira; Sugiman, (International Journal of Scientific Research and Management (IJSRM), 2025)
Integer is fundamental materials in mathematics learning. In addition to mastering basic materials, problem-solving ability and mathematical beliefs are important factors in mathematics learning. An effective learning strategy is necessary to enhance mathematical belief and problem-solving ability. This study aims to analyze the effectiveness of integrating Realistic Mathematics Education with Think Pair Share on problem-solving ability and mathematical beliefs in learning about integers. A Quasi-experimental study with a pretest-posttest control group design was conducted on 67 seventh-grade students randomly selected in Indonesia. Data collection for problem-solving ability utilized an essay test with 5 items, while for mathematical beliefs, a questionnaire of 24 statements with 4 answer choices was used. The results generalized that integrating Realistic Mathematics Education with Think Pair Share effectively enhances problem-solving ability and mathematical beliefs. The design of learning activities encouraged students to actively explore problems and interact to understand integer concepts. Developing various imaginable context based on Realistic Mathematics Education tenets is crucial to bridge the mathematics learning process.